Factor distribution pattern for some selected industries in Thailand - Alam, Khondakar Shamsul; Sharif, M. N.; Pakorn Adulbhan; Woo, Wai-Ling; Government of Switzerland (Bangkok : Asian Institute of Technology, 1974)
This research has been aimed at understanding the behavior of different industries of the developing countries in general and Thailand in particular with regard to different factor inputs, namely; employment, capitalization and energy, so that some general conclusions can be arrived at to aid the policy makers to design an effective industrial system. The specific purpose had been to attack the problem mathematically, so that a quantitative criteria could be developed to explain the behavior of industries both with respect to time and space. Attempts have been made to fit the factor inputs to common mathematical functions so that a quantitative relationship could be established to conform to statistical probability density functions. Gamma function was used to represent the behavior of the factor inputs for each industry on the basis of time and space, This was found to fit nicely. After fitting the gamma function mathematically, the function had been reduced to conform to statistical probability density functions and regression analysis was carried out for the parameters of the fitted gamma functions for statistical inferences and analysis of the factor inputs over the location of industries (space) and time period.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1974
Keywords: Industrialization -- Mathematical models